Evaluation of Risk Factors Related to Recidivism Among Sentenced Males - Yıldız, Sinem (The Bulletin of Legal Medicine, 2011)
Risk assessment is taking the place of dangerousness in recent criminal research. Detection of static and dynamic risk factors related and/or interacting to recidivism in accordance with personality characteristics and crime types may help crime prevention strategies to improve. Out of all participants 35% (n=41) are sentenced for manslaughter/physical injury, 35% (n=41) sexual crime and 30% (n=35) theft. The mean age of the participants is 33.81 (sd=9-12) years. During the interview, a questionnaire which is prepared by the researcher by reviewing the literature, Symptom Checklist Short Form, aggression inventory was used. Interviews are conducted face to face by the researcher at the relevant correctional facilities with the permissions of Ministry of Justice and ethical committee. Recidivism is found related to having a period far away from nuclear family before age 18, criminal and drag-alcohol abusing friends, anti-social behaviors; abusing illegal drags, displaying disciplinary problems in prison and during military service. Discussion: Results are evaluated under demographics, relationships in family and close friends, childhood abuse by leaning on current literature.Key words: prevention and control, crime, risk assessment
Keywords: prevention and control; crime; risk assessment